2022
DOI: 10.31219/osf.io/z3shb
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Switching between different cognitive strategies induces switch costs as evidenced by switches between manual and mental object rotation

Abstract: Switching between tasks incurs costs when compared to repeating the same task. It is unclear whether switch costs also occur when repeating the same task but switching the under-lying cognitive mechanism (CM). Here, we investigated whether such CM switch costs exist and whether possible CM switch costs impact how frequently participants switch between dif-ferent CMs. Specifically, we asked participants to judge the identity of two misaligned objects by either mental or manual computer-mediated object rotation.… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…However, when only comparing the present experiment with results from the same paradigm, differences vanish (i.e., 41% vs 43%, compare Figure 1g). However, in that study, participants showed the opposite perseveration pattern than in the present experiment: the iCM was preferred over the eCM (Figure 1g; Weis & Kunde, 2022). This opposite perseveration pattern might have been due to RT performance differences: While iCM use was slower than eCM use in the present study, iCM use was faster than eCM use in the former study 7 , which supports the idea that RT differences could be the driving force behind perseveration.…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…However, when only comparing the present experiment with results from the same paradigm, differences vanish (i.e., 41% vs 43%, compare Figure 1g). However, in that study, participants showed the opposite perseveration pattern than in the present experiment: the iCM was preferred over the eCM (Figure 1g; Weis & Kunde, 2022). This opposite perseveration pattern might have been due to RT performance differences: While iCM use was slower than eCM use in the present study, iCM use was faster than eCM use in the former study 7 , which supports the idea that RT differences could be the driving force behind perseveration.…”
Section: Discussionsupporting
confidence: 65%
“…Such perseverations on one of both mechanisms are reflected by a bimodal distribution. In particular, data was obtained from joint arithmetic and social problem solving with a telepresent agent (a; Weis & Herbert, 2022), from solving alphanumeric problems with or without help from a computer (b; Weis & Wiese, 2019a), from intention offloading with or without spatial manipulation on a computer screen (c-f Scarampi & Gilbert, 2020), and from an object rotation task with mental or manual computer-mediated rotation (g; ` Weis & Kunde, 2022). Dashed gray lines represent means.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations